Mitomycin and 5‐fluorouracil for second‐line treatment of metastatic squamous cell carcinomas of the anal canal. (16th September 2019) - Saint, Angélique; Evesque, Ludovic; Falk, Alexander T.; Cavaglione, Gérard; Montagne, Lucile; Benezery, Karen; Francois, Eric
Abstract: Background: Metastatic squamous cell carcinomas (SCC) of the anal canal are rare and there is no international consensus on their second‐line management. 5‐Fluorouracil (5‐FU) and mitomycin in combination with radiotherapy is the standard for locally advanced forms but its efficacy in metastatic stage has never been evaluated. Patients and methods: We report a retrospective analysis of patients treated with 5‐FU and mitomycin from 2000 to 2017 in our institution for a metastatic SCC of the anal canal after failure of platinum‐based regimen. The main outcome was progression‐free survival (PFS) and the secondary outcomes were overall survival (OS), response rate, and toxicity. Results: Nineteen patients, 15 women and four men, with a median age of 57 years were identified (range, 40‐79 years). Patients received a median of three cycles (1‐7) of mitomycin 5‐FU. A dose reduction was necessary in six patients (31.6%), one patient had to discontinue treatment following toxicity and no death was due to treatment toxicity was reported. An objective response was observed in five patients (26.4%, 95% CI 6.6‐46.2) including one complete response, six patients (31.6%, 95% CI 10.7‐52.5) showed tumor stabilization. Median PFS and OS were 3 months [95% CI 1‐5] and 7 months [95% CI 2.2‐11.8]. Responder had a median duration of response of 4 months [95% CI 1.8‐6.1] and one patient had 23 months duration of response. No significant difference was noted for PFS and OS for patients previously treated with mitomycin and 5‐FU at a local stage. Conclusion: Mitomycin and 5‐FU regimen provides tumor control with acceptable tolerance. It is an option for patients with metastatic SCC of the anal canal after failure of platinum‐based chemotherapy. [Correction added on 9 October 2019, after first online publication: '5‐FU' was inadvertently removed from the Results and Conclusion and has now been added to the text.] Abstract : 5‐Fluorouracil and mitomycin in combination with radiotherapy is the standard for locally advanced squamous cell carcinomas of the anal canal and we have evaluated its efficacy in metastatic stage. This study is a retrospective analysis of patients treated with and mitomycin from 2000 to 2017 in our institution for a metastatic SCC of the anal canal after failure of platinum‐based regimen. Mitomycin and 5‐FU provides a Response Evaluation Criteria in Solid Tumors response in nearly a quarter of patients with acceptable toxicity. It is a reasonable therapeutic option after failure of a first‐line chemotherapy in the absence of other therapeutic option.